QUALITY MANAGEMENT SYSTEM AT CONSTRUCTION PROJECT - Mat Naim Abdullah @ Mohd. Asmoni, 1969-, author; Miswan @ Abdul Hakim Mohammed 1959-2021 author 556897; Mohd. Nadzri Jaafar author 492451; Rehmaashini Jagarajan, 1987-, author 598141 (Johor Bahru, Johor : Penerbit UTM Press, 2017)
Includes bibliographical references and index